Modeling of Boiler Drum for the Design of Drum Level Control -A System Identification Approach - Sumalatha A, A Bhujanga Rao (International Journal of Advanced Science and Technology, 2020)
The boilers are the heart of the thermal power generation plants. Achieving optimal control of process loops is significant especially in coal fired thermal power plants. Model based control is more advantageous due its flexibility in the design of control system. Experimental determination of boiler drum model through system identification approach is presented in this paper. Dynamic models obtained from real time process data are useful in the design of robust control systems. Process data collected from Dr.Narla Tata Rao Thermal Power Plant is utilized for obtaining the dynamic model of coal fired boiler and the results are presented. Matlab/Simulink is used for extract the dynamic model from plant process data. Models obtained from various operating points were presented for comparison.